(3JaSjQ ZQjH GdbQBfs - (3CHh HcQ eMeO Hf YRjR GdSLSJGfjs ((3WjH Hf dDdD GdcMGNi s)
(3ChdgG (B:s
(3gPG cJGH ZQjH GdbQBf Cda Ydi MQha GdeYLe djbQH JfGhdg hjSgd JMaXg Ydi ef CQGOg hHGddg GdJhajb PcQ GdgeRI GdeaJhMI Cde hSGFQ MQha GdgLGA s
(3BNQgG (B:s
(3GdjGA GdecShQI bjd djS ai cdGe GdYQHjI cdeI ChdgG jGA ecShQg EdG jSGQ hjTGQ ddjO Je GdcJGH HMeO Gddg JYGdi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs